Professional Competence of Elementary School Teachers in Teaching Mathematics by Utilizing Motor Skills - Mardani, Sri; Riyadi, Riyadi; Budiarti, Indah Slamet (Universitas Sebelas Maret, 2024)
This study describes the level of professional competence of teachers in teaching mathematics in elementary schools by utilizing motor skills. The main purpose of this study is to explore and describe the stages of building mathematical concepts through motor skills. This type of research is descriptive qualitative which aims to explain in detail the stages of building mathematical concepts in elementary schools through motor skills. Data were collected through field observations, questionnaires, and interviews. The results showed that: 18 out of 20 teachers (90%) do not understand the motor skills of stepping and jumping as an activity to understand mathematical operations; 17 out of 20 teachers (85%) have a wrong understanding that generalizes the motor skills between Numerical and Round numbers are the same; 19 out of 20 teachers (95%) have an understanding of mathematical operations on Round numbers with memorization methods